Peran Corporate Social Responsibility (CSR) PT. Kanitra Mitra Jayautama Di Desa Mulawarman, Kutai Kartanegara Kalimantan Timur - Daniel Jaya Jagad; Mahmud; Ibnu Mundzir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the implementation of the Corporate Social Responsibility (CSR) program Bebas Stunting (BeSti) by PT. Kanitra Mitra Jayautama in Mulawarman Village, Kutai Kartanegara, East Kalimantan. The program aims to improve community welfare, particularly in health, economic, and social sectors. This qualitative descriptive research involved interviews, observations, and document analysis from key stakeholders including villagers, company employees, and local government representatives. The findings show that the CSR program had a positive impact, notably through the Supplementary Feeding Program (PMT) in reducing stunting, small business training for economic empowerment, and employee involvement in social activities that fostered stronger community ties. However, the program also faced several challenges, including limited resources, low community engagement, and weak coordination among stakeholders. The study recommends further research using quantitative methods to measure the impact of CSR on specific welfare indicators such as health improvements and per capita income. Additionally, future studies should examine the sustainability of CSR initiatives and the effectiveness of stakeholder collaboration to enhance long-term outcomes.